Kelimpahan Kepiting Scylla sp. di Kawasan Hutan Mangrove Desa Lalombi Kecamatan Banawa Selatan Kabupaten Donggala dan Pemanfaatannya Sebagai Media Pembelajaran - Khaerunnisa; Bustamin; Abd. Rauf; Achmad Ramadhan; Moh. Sabran; Manap Trianto (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the abundance of Scylla sp. crabs in the mangrove forest area of ​​Lalombi Village, South Banawa District, Donggala Regency. The type of research used is descriptive quantitative. The technique for determining the location for sampling is using the purposive sampling method. Sampling of Scylla sp. crabs was carried out directly by hand collection method at low tide. The population and samples in this study were all types of Scylla sp. crabs found in the research location. Data analysis was carried out by calculating the abundance index, to determine the level of abundance of the crab species found. The Scylla sp. crab samples obtained amounted to 4 species, namely Scylla tranquebarica with an abundance index of 46%, Scylla paramamosain with an abundance index of 36%, Scylla olivacea with an abundance index of 43%, and Scylla serrata crabs are the most abundant crab species with an abundance index of 49%. The abundance index value of Scylla sp. crabs obtained in the mangrove forest area of ​​Lalombi Village, South Banawa District, Donggala Regency shows a moderate level of abundance.